EFEKTIVITAS PEMBELAJARAN BAHASA INDONESIA DENGAN METODE LOMPAT CERDAS BAGI SISWA KELAS 6 MI MA’ARIF NU 2 SANGGREMAN - Yuli Setiyani (Pusat Studi Pendidikan dan Kreatifitas Anak Purwokerto, 2020)
Learning Indonesian is often taken lightly by students. Students in learning are not very enthusiastic, but in fact when the implementation of the test results have not reached the expected target. This is certainly a special concern for teachers to foster student interest, especially in class 6 MI Ma'arif NU 2 Sanggreman. The ideal step is to present effective and enjoyable Indonesian learning, especially because Grade 6 is facing a national exam so it must master Indonesian language learning materials well. The implementation of this research uses a qualitative method that presents and analyzes data descriptively. Data collection methods use observation, interviews, and documentation. Data analysis uses Miles and Hubberman data analysis. The results of the study, while being evaluated by carrying out frog jumps, the result is the number of students who can take part in Indonesian language learning activities that look active as much as 80%. From these results it can be concluded that the implementation of Indonesian language learning using the smart jump method is effective because in it there is quality of learning, suitability, intensive, and time.